The EU and Cyprus : principles and strategies of full integration - Laulhé Shaelou, Stéphanie (Studies in EU external relations ;, 2010)
The European integration of Cyprus is the outcome of a process commenced over thirty years ago within the context of the EC external trade relations, culminating in Cyprusa (TM) accession to the EU in 2004 and still ongoing within the framework of the EU external relations. The key issue concerns the achievement of a ~fulla (TM) integration arguably through a mode of European integration re-formulating traditional parameters of economic, societal and political integration. Beyond the obvious academic interest arising out of a comprehensive comparative socio-legal study of the process of Europe.